Lagrange multiplier approach for excited state properties through intermediate hamiltonian formulation of fock space multireference coupled-cluster theory - Gupta, Jitendra; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2013)
In this paper, we present a formulation based on Lagrange multiplier approach for efficient evaluation of excited state energy derivatives in Fock space coupled cluster theory within the intermediate Hamiltonian framework. The formulation is applied to derive the explicit generic expressions up to second order energy derivatives for [1, 1] sector of Fock space with singles and doubles approximation. Its advantage, efficiency, and interconnection in comparison to the Lagrange multiplier approach in traditional formulation of Fock space, which is built on the concept of Bloch equation based effective Hamiltonian, has been discussed. Computational strategy for their implementation has also been discussed in some detail. (C) 2013 AIP Publishing LLC.